A qualitative analysis of the experiences of people with psychosis of a novel cognitive behavioural therapy targeting suicidality. Issue 1 (2nd January 2017) - Awenat, Yvonne F.; Shaw-Núñez, Emma; Kelly, James; Law, Heather; Ahmed, Sehar; Welford, Mary; Tarrier, Nicholas; Gooding, Patricia A.
Abstract: This study presents a qualitative evaluation of a novel cognitive behavioural therapy targeting suicidal thoughts and behaviours for people experiencing psychosis. Eight participants from four NHS Trusts in the northwest of England were interviewed. The interview schedule was collaboratively developed with a Service User Reference Group whose membership included people with experience of psychosis. Thematic analysis captured participants' experiences of recovery from suicidal thoughts and behaviours following therapy. Two themes were identified: "Acceptability" depicted participants' views about the process of therapy and the therapeutic relationship; "In-recovery from suicidality" illustrated participants' views of the impact of the therapy.